2020
DOI: 10.7150/jca.40961
|View full text |Cite
|
Sign up to set email alerts
|

High Preoperative Plasma Fibrinogen Independently Predicts a Poor Prognosis in Patients with Nonmetastatic RCC

Abstract: Background: This study aims to determine the relationship between preoperative plasma fibrinogen levels and the prognosis of patients with nonmetastatic renal cell carcinoma (RCC), including overall survival (OS), cancer-specific survival (CSS) and progression-free survival (PFS). Methods: We retrospectively analysed the clinical data and prognostic information of 1194 nonmetastatic RCC patients who received radical nephrectomy or nephron-sparing surgery between 2005 and 2015 at our institution. Serum was coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…As these prognostic factors are not well established, clinicians have now been focusing on novel markers, including laboratory and clinical indicators. Studies have shown that laboratory indicators, such as platelets, neutrophil lymphocyte ratio, plasma fibrinogen, D‐dimer, and serum albumin/globulin ratio are effective in assessing the prognosis of RCC 8–12 . However, most of the studied biomarkers cannot be widely used in the clinic because of their taught difficult measurements and expensive price, so we need to focus on “new” methods such as preoperative serum cystatin‐c levels.…”
Section: Introductionmentioning
confidence: 99%
“…As these prognostic factors are not well established, clinicians have now been focusing on novel markers, including laboratory and clinical indicators. Studies have shown that laboratory indicators, such as platelets, neutrophil lymphocyte ratio, plasma fibrinogen, D‐dimer, and serum albumin/globulin ratio are effective in assessing the prognosis of RCC 8–12 . However, most of the studied biomarkers cannot be widely used in the clinic because of their taught difficult measurements and expensive price, so we need to focus on “new” methods such as preoperative serum cystatin‐c levels.…”
Section: Introductionmentioning
confidence: 99%